BITCOIN LAW AS AN INVESTMENT ASSET IN THE ERA OF DIGITAL ECONOMY - Nadirah, Ida (Proceeding International Seminar of Islamic Studies, 2024)
This article is to find out the law of bitcon as a currency that is widely used as a means of payment and public investment in the era of the digital economy. From the data obtained now the use of bitcoin there are already around 200,000 Bitcoin investors in Indonesia who at least represent transaction flows worth Rp. 4,000,000,000, (four billion) per day.  Bank Indonesia as the authority in the financial sector states that bitcoin is not a legal currency that can be used for transactions in trade so that this will create a legal vacuum. The approach method used in this study is a normative approach by reviewing applicable laws and regulations relating to bitcoin currency. The data source used is secondary data from the results of literature research which is then analyzed qualitatively. The results showed that public ignorance of bitcoin's legal position as a means of payment in trading and investing will have an impact on the bitcoin user community not getting legal protection. For this reason, it needs socialization and education from the government so that people are not deceived in the use of bitcoin.